Analisis Kualitas Layanan Frontliner Terhdap Pertumbuhan Dana Pihak Ketiga Studi Pada PT Bank Syariah Mandiri Cabang Bekasi Pondok Gede - Gumilang, Haryo; Putra, Purnama (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
The main activity of the bank is the provision of services. Banks as financial institutions engagedin services, must be able to provide the best service (Service Excellence) in order to win competitionin increasingly competitive situations. Frontliners are officers who are in front of the banking hallthat face directly to customers. This study aims to analyze how much influence the quality of serviceFrontliner (Customer Service, Teller, Security) on the growth of third party funds. In this studyusing primary and secondary data obtained from the official website of Bank Syariah Mandiri andquestionnaires distributed to respondents. The method used is a quantitative method. The results ofthis study show partially that the quality of frontline service (Customer Service, Teller, Security) hasa positive effect on third party funds. While simultaneously the quality of Customer Service services,Teller service quality, security service quality has a significant positive effect on the growth of thirdparty funds. Future research is expected to expand the scope of research or compare variables andother factors.